Long-run forecasting of the number of the ecotourism arrivals in the municipality of Stambolovo, Bulgaria - Dimitrov,Preslav (2013)
Most of the Bulgarian rural municipalities need to back up their investment decisions in tourism infrastructure by preliminary analysis and forecasts. The present paper regards several major problems in the application of exponential smoothing methods for the purpose of the long-run forecasting for the needs of the mountainous municipality of Stambolovo, Bulgaria, such as: (i) the problem of determining the time series pattern; or the so-called “forecast profile”; (ii) the selection of a suitable forecasting method; (iii) Calculating of short-run and long-run forecasts; and (iv) the comparison of the results of the forecast techniques on the basis of the errors in the forecasts. A specially designed model for estimation of the weight coefficient needed for determining the size of the rural tourism and ecotourism sectors of this very same municipality, located near Bulgaria’s border with Greece and Turkey, is being presented.